2021
DOI: 10.1111/jen.12874
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational playbacks and microscopy to study the signalling behaviour and female physiology of Philaenusspumarius

Abstract: The meadow spittlebug Philaenus spumarius, vector of the bacterium Xylella fastidiosa, relies on vibrational communication to accomplish mating: the female calls to establish a duet with a male. A deeper knowledge of the species’ reproductive biology and behaviour would provide useful information for developing control techniques based on principles of ‘biotremology’, which studies the vibrational behaviour of animals. Playback tests were conducted on single females and male–female pairs of P. spumarius from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
4
14
0
Order By: Relevance
“…On the other hand, although the male courtship is usually emitted by males in response to female calling signals [ 23 ], it was produced by males in the absence of females during our trials. The same behavior was also observed in absence of other males and in response to playbacks of male signals [ 24 ]. It is possible that the male calling signal triggered other males to produce courtship signals, due to similarities with the female calling (i.e., they are both composed of chirps).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…On the other hand, although the male courtship is usually emitted by males in response to female calling signals [ 23 ], it was produced by males in the absence of females during our trials. The same behavior was also observed in absence of other males and in response to playbacks of male signals [ 24 ]. It is possible that the male calling signal triggered other males to produce courtship signals, due to similarities with the female calling (i.e., they are both composed of chirps).…”
Section: Discussionsupporting
confidence: 56%
“…This study investigated intrasexual communication and associated types of vibrational signals occurring in non-social insect groups. Under semi-field conditions (e.g., natural daylight and temperatures), the signaling behavior of P. spumarius females was recorded from the 24th of July 2018, earlier than a previous study in laboratory conditions that reported the occurrence of female mating signals from August, in correspondence with the maturation of their reproductive apparatus [ 24 ]. Females produced intersexual vibrational signals, when tested alone, in the presence of another male or when subjected to a playback only when they were sexually mature.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Regarding the manipulation of sexual behavior, interesting investigations are ongoing to characterize the emission of vibrational signals by males and females. The first detailed description of the vibrational signals with specific roles within the mating behavior of P. spumarius was reported by Avosani et al [ 101 ]. The authors concluded that even if further research is needed to identify an efficient signal and the most suitable strategy for field application, these preliminary results open up the possibility to manipulate P. spumarius behavior through artificial playbacks and for the future development of low environmental impact control practices, for example by attracting males into a trap using a specific vibrational signal.…”
Section: Current Attempts To Control the Insect Vector(s) In Olives—state Of The Artmentioning
confidence: 99%